2019
DOI: 10.1177/0003489419896379
|View full text |Cite
|
Sign up to set email alerts
|

Supraglottoplasty in Neonates under One Month of Age

Abstract: Objectives: Examine outcomes of patients 1 month of age or less who received supraglottoplasty. Demonstrate the feasibility and safety of supraglottoplasty in neonates <1 month of age. Methods: Charts were reviewed from 2015-2017. Patients with previously identified laryngomalacia requiring surgical intervention and age 1 month or less were identified. We collected data on age, gender, surgical technique, other airway lesions, time to extubation and discharge, and comorbidities. Results: Six patients met th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Younger age was observed in patients admitted to the PICU in the studies included in our review, but not found to be statistically significant. However, in two studies specifically investigating young patients undergoing supraglottoplasty (less than 2 months), age was found to be associated with a more difficult post-operative course, including prolonged intubation, which corresponds with the observations made in our studies [23,25].…”
Section: Patient Factorssupporting
confidence: 89%
“…Younger age was observed in patients admitted to the PICU in the studies included in our review, but not found to be statistically significant. However, in two studies specifically investigating young patients undergoing supraglottoplasty (less than 2 months), age was found to be associated with a more difficult post-operative course, including prolonged intubation, which corresponds with the observations made in our studies [23,25].…”
Section: Patient Factorssupporting
confidence: 89%